Tinjauan Teoritis Pendidikan Akidah dalam Keluarga sebagai Strategi Pencegahan Internet Gaming Disorder (IGD) - Irhas (Yayasan Dharma Lentera Khatulistiwa (MALEWA), 2025)
This study is a theoretical review that aims to examine the role of faith education in the family as a strategy for preventing Internet Gaming Disorder (IGD) in children. IGD is an addictive behavioural disorder that increasingly threatens children's psychosocial development in the digital age. The family, as the first educational institution, has a strategic role in shaping children's faith and self-control to avoid addictive behaviour. This article shows that religious education contributes to strengthening children's self-control through the instillation of monotheistic values, moral awareness, and self-regulation based on faith. The principle of monotheism also plays a role in building digital awareness, namely the ability of children to use technology proportionally and not make it an object of emotional dependence. This study recommends strategies for implementing religious education in the family, including instilling values, setting an example, providing digital guidance, and strengthening religious communication as preventive measures against the risks of IGD. These conceptual findings confirm that strengthening religious beliefs in the family has significant potential in shaping healthy digital behavior and preventing addictive tendencies in online gaming.